An exploratory study of the impact of scarring on sexuality and body image of females who have sustained a burn injury - Connell, Kylie (Curtin University, 2014)
This study explores how burn injuries impact sexuality, body image and interpersonal relationships in females. A sequential, mixed methods research design was used to identify potential correlations between the incidence of poor sexual esteem, sexual avoidance and satisfaction with life and increased body image dissatisfaction in female burn survivors. Female burn survivors are at risk of sexuality and body image dissatisfaction post injury, which is long standing and independent of improvement in physical function.